Leveling the Playing Field? Communication Technology as a Predictor of Future Attainments for Deaf Young Adults - Carrie Lou Garberoglio; Duncan Dickson; Stephanie Cawthon; Mark Bond (Disability Studies Quarterly, 2015)
Communication technologies are often proposed to level the playing field for individuals with disabilities, but the benefits may be magnified for deaf individuals in particular due to the communication barriers experienced by these individuals. In this paper, we set out to test the assumption that increased engagement with communication technology, specifically computer-mediated communication, during adolescence would contribute to actual attainment gains in adult life for deaf individuals in three domains: life, education, and employment. A secondary analysis using the National Longitudinal Transition Study 2 (NLTS2) was conducted, allowing for a longitudinal examination of deaf individuals' experiences in the transition from adolescence to adulthood. Findings revealed that deaf individuals who engaged with computer-mediated communication at higher frequencies during adolescence did not reveal discernible gains in adult life attainments in any domain. We propose that the benefits of communication technology only go so far, and that achieving greater equitable outcomes for deaf individuals requires larger systemic change.
Keywords: communication technologies; deaf; young adults; adult life attainments